Private rhino conservation: Diverse strategies adopted in response to the poaching crisis. Issue 6 (15th June 2020) - Clements, Hayley S.; Knight, Mike; Jones, Pelham; Balfour, Dave
Abstract: Private landowners in South Africa conserve roughly 40% of white rhinos globally. Given concerns that escalating poaching has caused private‐rhino owners to disinvest, we used a national survey to assess 171 private‐rhino owners' responses to the crisis. Twenty‐eight percent of rhino owners are disinvesting in rhino, 57% are pursuing business‐as‐usual (largely ecotourism), and 15% are investing in more rhinos. It is currently unclear whether this diversity in private‐rhino owners' responses to the crisis is increasing the resilience of the rhino population to poaching. Some rhino investors show signs of financial stress. Most owners support rhino‐horn trade to fund conservation, yet international trade remains banned. By contrast, a recent national policy amendment allows rhinos to be managed as livestock, risking a shift from rhino‐for‐conservation to rhino‐for‐production on private land. Our findings highlight an urgent need to ensure policies keep pace with dynamic socioeconomic environments that influence the sustainability of wildlife use.